AGING MANAGEMENT WITH THE USE OF EXOSOMES, PRP/PRF WITH ALBUMIN GEL (PLASMA GEL) AND ASSOCIATED TECHNIQUES IN OROFACIAL HARMONIZATION TREATMENT - Maso, Adelaide (Health and Society, 2024)
Aging, it is a physiological process that involves a progressive decline in the function of the organs, with loss of homeostasis and increased likelihood of disease disease and death. This account focuses on the classic perspectives on the biogenesis of exosomes, and age-related associated changes. Due to its ability to transmit biological information between cells, this work also discusses the interaction of mesenchymal cell exosomes, as a potent adjuvant in the treatment of association of orofacial harmonization techniques. The demand for aesthetic and rejuvenating treatments is increasing in society, thus, each day, the demand for orofacial harmonization increases exponentially in order to slow aging. Orofacial harmonization is a set of procedures performed by the dentist, which aims at the aesthetic and functional balance of the face. Exosomes are membranous extracellular vesicles ranging from 30 to 200 nm in diameter. Exosomes has been found to be secreted by most cell types, including immune cells (B cells, T cells, mastocytes, dendritic cells), neuronal cells, epithelial cells, endothelial cells, embryonic cells, cancer cells and cells mesenchymal trunk (mscs). The search for youth and perfect skin is a natural desire for the human being. And in this way, collagen biostimulation stands out as a safe and effective option to rejuvenate the skin, fighting the signs of aging and promoting a firmer, toned and radiant appearance. Research in exosomes therapies continues to prosper. Subsequent data on indications, dose response, safety, effectiveness and ability to combine therapy with exosomes as a “skin primer” for biostimulation techniques, such as calcium hydroxylapatite (CAHA), platelet rich plaketers (PRP) and fibrin matrix Platelet plasma, (PRFM) is growing rapidly.